Heritability of Phenotypes Associated with Glucose Homeostasis and Adiposity in a Rural Area of Brazil. (January 2014) - Pena, Geórgia G.; Dutra, Míriam Santos; Gazzinelli, Andrea; Corrêa‐Oliveira, Rodrigo; Velasquez‐Melendez, Gustavo
Summary We aimed to estimate the heritability and genetic correlation between glucose homeostasis and adiposity traits in a population in a rural community in Brazil. The Jequitinhonha Community Family Study cohort consists of subjects aged ≥18 years residing in rural areas in Brazil. The data on the following traits were assembled for 280 individuals (51.7% women): body mass index (BMI), body fat percentage, waist and mid‐upper arm circumferences, triceps skinfold, conicity index, insulin, glucose, high‐density lipoprotein cholesterol (HDLc), triglycerides and C‐reactive protein. Extended pedigrees were constructed up to the third generation of individuals using the data management software PEDSYS. The heritability and genetic correlations were estimated using a variance component method. The age‐ and sex‐adjusted heritability values estimated for insulin (h2 = 52%), glucose (h2 = 51%), HDLc (h2 = 58%), and waist circumference (WC; h2 = 49%) were high. Significantly adjusted genetic correlations were observed between insulin paired with each of the following phenotypes; (BMI; ρg = 0.48), WC (ρg = 0.47) and HDLc (ρg = −0.47). The homeostasis model assessment of insulin resistance (HOMA‐IR) was genetically correlated with BMI (ρg = 0.53) and HDLc (ρg = −0.58). The adjusted genetic correlations between traits were consistently higher compared with the environmental correlations. In conclusion, glucose metabolism and adiposity traits are highly heritable and share common genetic effects with body adiposity traits.